2013
DOI: 10.1155/2013/238734
|View full text |Cite
|
Sign up to set email alerts
|

Hemeoxygenase-1 Mediates an Adaptive Response to Spermidine-Induced Cell Death in Human Endothelial Cells

Abstract: Spermidine (SPD) is a ubiquitous polycation that is commonly distributed in living organisms. Intracellular levels of SPD are tightly regulated, and SPD controls cell proliferation and death. However, SPD undergoes oxidation in the presence of serum, producing aldehydes, hydrogen peroxide, and ammonia, which exert cytotoxic effect on cells. Hemeoxygenase-1 (HO-1) is thought to have a protective effect against oxidative stress. Upregulation of HO-1 in endothelial cells is considered to be beneficial in the card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…It is well known that activation of PI3K/AKT signaling functions as a cytoprotective mechanism against oxidative stress (Mo et al 2012, Ryu et al 2014, Yang et al 2013. In this sense, our results demonstrated that, in addition to stimulating Hmox1 gene expression, treatment of Y1 cells with either ACTH or 8Br-cAMP also leads to an increase in Akt phosphorylation levels.…”
Section: Discussionsupporting
confidence: 72%
“…It is well known that activation of PI3K/AKT signaling functions as a cytoprotective mechanism against oxidative stress (Mo et al 2012, Ryu et al 2014, Yang et al 2013. In this sense, our results demonstrated that, in addition to stimulating Hmox1 gene expression, treatment of Y1 cells with either ACTH or 8Br-cAMP also leads to an increase in Akt phosphorylation levels.…”
Section: Discussionsupporting
confidence: 72%
“…HO originally functions as a rate-limiting enzyme in heme degradation, yielding carbon monoxide (CO), iron, and biliverdin as the end products. HO-1 and HO-2 are isoforms of HO in mammals [1]. The HO-2 isoform is constitutively expressed; however, HO-1 is an inducible one.…”
Section: Introductionmentioning
confidence: 99%
“…By exploring the inner connection of these metabolic pathways, 26 metabolic pathways associated with AKT pathways are found. AKT is activated by a number of receptor tyrosine kinases following the binding of growth factors or hormones such as PDGF and insulin, working as an important mediator of the 3-phosphoinositide-dependent kinase (PI3K) pathway [30][31][32][33]. Activated AKT can increase the expression of many pro-proliferative genes such as Bcl-2, decrease pro-apoptotic genes (Kv channels), and then lead to PAH [34].…”
Section: Discussionmentioning
confidence: 99%